Island beneath the sea : a novel - Allende, Isabel; Peden, Margaret Sayers (New York : Harper, 2010)
"The story of a mulatta woman, a slave and concubine, determined to take control of her own destiny in a society where that would seem impossible"--Provided by publisher.
Keywords: Racially mixed women -- Fiction; Women slaves -- Fiction; Sugar plantations -- Fiction; Plantation life -- Fiction; Haiti -- Fiction; Caribbean Area -- Fiction